Teaching web technologies: understanding the tutor's perspective. (2nd January 2019) - Douce, Chris
Abstract: This paper describes an Open University eSTEeM project that gathered the experiences of computing and information technology tutors who teach an undergraduate module called Web Technologies with the intention of understanding more about how they and their students can be best supported. Twelve distance learning tutors were interviewed by two interviewers. The interviews were transcribed and then thematically analysed. It was discovered that some tutors hold the view that some of their students struggle to understand aspects of the technologies that are being taught. It was also apparent that tutors have very different approaches when using certain tools to teach web technologies to students. The paper concludes by summarising key findings, presenting potential enhancements and suggesting further research directions.